Exploring essential factors of learning spaces and its relationships to academic performance in the Philippine Public Secondary School System - Reyno, Renzo Edrian G.
Despite the extensive efforts of the Philippine education sectors with the implementation of the K-12 Curriculum, the present state of academic proficiency levels is stagnating. This may equate to less adept Filipinos as the students of the present are the main citizens of the Philippines in the future. Radcliffe (2008) defined the elements of learning in the 21st century; Pedagogy, Technology, and Space. There are evident investments on pedagogy and technology but not much in the space. Lipset (2007) confIsidoro R. Malaque IIIed that learning spaces are more to blame for school failures than teachers. Thus, this study explored the learning space with its factors and relationships with the academic performance of learners of the public secondary schools in Davao City. The study utilized meta-analysis of existing Learning Space Factors (LSFs) as standards for evaluating the learning spaces and ConfIsidoro R. Malaque IIIatory Factor Analysis (CFA) to confIsidoro R. Malaque III these LSFs. Additionally, Exploratory Factor Analysis (EFA) was also performed to discover more LSFs that are evident and unique to the Filipino learners and the Philippine setting. The relationships of the learning spaces and academic performance are defined through Pearson correlation. The study defined 12 LSFs specifically; learning climate, learning facility, spatial configuration, learning space vulnerability, domesticity, interface, proxemics, integrated technology, mobility, and location and vicinity. Findings depict the directly proportional relationship between the learning space and the Filipino learners. The quality of learning spaces significantly affects the academic performance of the Filipino students. Furthermore, the study discovered that other than existing formal learning spaces, Filipino students also utilize the interfaces and outdoor environments as vital learning spaces. Architectural design guidelines were generated on how to improve and maximize the learning space in the Philippine public secondary school setting and proposed a project of strategic integration of system-based teaching environments for maximizing achievement.